Draft Annual Plan 1988-89 (Statements) Vol.-III Government of Manipur - Planning Commission (Planning Commission, 1987)
Outlay & Expenditure (head/sub-head of development) Outlay & Expenditure (development schemes/projects/major/minor heads) Physical Target & Achievement Outlay & Expenditure (minimum needs Programme) Physical Target Achievement (minimum needs Programme) Outlay & Expenditure (Centrally Sponsored Scheme) Outlay & Expenditure under triba1 sub-plan Physical Target & Achievement under tribal site-plan Employment content of sectoral Programme(outlay and expenditure) Employment content of sectoral Programme (physical target & achievement).
Government of Manipur, Planning Department